2022
DOI: 10.3389/fevo.2022.804118
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Integration Between Colour Theory and Biodiversity Values in the Design of Living Walls

Abstract: Designing green infrastructure in cities requires vegetation that has multiple outcomes and functions, particularly using plants that have both attractive visual or aesthetic features and high biodiversity values. Plantings that have high visual appeal are more highly valued by people and increase their feeling of wellbeing. Increasing biodiversity in cities is one of the major challenges facing urban planning and design. However, balancing biodiversity and aesthetic outcomes in urban planting design is comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
0
2
0
2
Order By: Relevance
“…A colour composition with these qualities might lead to perceived pleasurable experiences, relaxation and positive expectations for butterflies, bumblebees, bees, and other insects. Earlier studies have shown the importance of a well-balanced understanding of colour theory and awareness of related human experiences to reach positive visual aesthetic outcome and restorative effects (Neale et al, 2021;Thorpert et al, 2022). This indicates that the link between human visual perception, aesthetic and restorative qualities, and colour characteristics should not be neglected in design issues and planning programmes.…”
Section: Discussionmentioning
confidence: 99%
“…A colour composition with these qualities might lead to perceived pleasurable experiences, relaxation and positive expectations for butterflies, bumblebees, bees, and other insects. Earlier studies have shown the importance of a well-balanced understanding of colour theory and awareness of related human experiences to reach positive visual aesthetic outcome and restorative effects (Neale et al, 2021;Thorpert et al, 2022). This indicates that the link between human visual perception, aesthetic and restorative qualities, and colour characteristics should not be neglected in design issues and planning programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Biodiversity can certainly be promoted using animal-aided design, water supply, and the right plant choice. Thorpert et al (2022) pointed out that choosing plants for living walls with the color theory is possible and that the plants could promote biodiversity simultaneously. Moreover, the creation of LWs, which provides a great temperature-lowering effect, is an appropriate consideration in the context of climate change and heat stress in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Bujna zieleń i kolorowe nasadzenia stanowią wyraźny kontrast, wobec betonowych i szklanych struktur, tworząc harmonijne i estetyczne krajobrazy miejskie. Ta wizualna różnorodność, przyczynia się do poprawy ogólnej atrakcyjności miejskich obszarów [40].…”
Section: Zwiększanie Atrakcyjności Estetycznejunclassified
“…Dynamiczny charakter zielonych ścian, związany z różnorodnością gatunków roślin i sezonowymi zmianami w liściach i kwitnieniu [40], dodaje kolejny walor estetyczny. To ciągłe przemienianie się krajobrazu przez cały rok, czyni miejskie przestrzenie bardziej intrygującymi i atrakcyjnymi.…”
Section: Zwiększanie Atrakcyjności Estetycznejunclassified